Autocontrol como predictor de las agresiones autoinformadas entre pares en estudiantes de primaria y secundaria en Medellín, Colombia - Morillo Puente, Solbey (2024)
Self-control is the most influential construction in antisocial behavior and aggression among peers with antisocial behaviors. The relationship between assaults and self-control was investigated in 265 students in Colombia, through a quantitative survey with a self-reporting survey. 29.8% of participants were under self-control, and one in ten participated in the aggression studied. Low self-control is significantly linked to these assaults, and sex to relational assault, but not to physical or verbal. Furthermore, Self-Control has a greater specific weight in predicting physical assaults, while age has the highest specific weight for verbal and relational assault. It is concluded that self-control predicts the variable self-informed physical and verbal aggression, but not the relational.